2018
DOI: 10.1177/1938640018810419
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Open Reduction and Internal Fixation of Ankle Fractures

Abstract: Background. Unstable ankle fractures are treated with open reduction internal fixation (ORIF) to prevent posttraumatic arthritis. Typically, ORIF is performed as an ambulatory surgery several days to a few weeks after injury. It is unclear what effect this delay may have on functional outcome. This study aimed to assess the effect of timing of ankle ORIF on wound complications and functional outcome. Methods. A retrospective review of 121 patients who underwent ankle ORIF was performed. A total of 58 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…Prior studies assessing the effects of timing on fracture fixation on outcome have used cutoffs including 24 hours, 1–2 weeks, and 5 weeks to discriminate between early versus delayed fixation. 17 , 18 , 19 , 20 However, these studies are limited, and only one study to date has defined delayed fixation for upper extremity fracture as 14 days. 20 This study defined delayed fixation similarly as greater than 14 days from injury, early fixation was defined as fracture fixation within 3 days of injury, and standard fixation was defined as fixation between 3 and 14 days from time of injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies assessing the effects of timing on fracture fixation on outcome have used cutoffs including 24 hours, 1–2 weeks, and 5 weeks to discriminate between early versus delayed fixation. 17 , 18 , 19 , 20 However, these studies are limited, and only one study to date has defined delayed fixation for upper extremity fracture as 14 days. 20 This study defined delayed fixation similarly as greater than 14 days from injury, early fixation was defined as fracture fixation within 3 days of injury, and standard fixation was defined as fixation between 3 and 14 days from time of injury.…”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to other studies that have shown no differences in outcomes after ankle fractures with regards to early versus delayed fixation. 17 , 18 Additionally, a recent systematic review assessing the effect of time-to-surgery on distal radius fracture outcomes found significantly inferior Disabilities of the Arm, Shoulder, and Hand scores among patients who underwent surgery 14 days after injury, but there were no differences in complication or revision rates. 20 The current study also found a significant association between everyday smoking and total complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical soft tissue characterization when managing severely injured limbs remains challenging and has a large subjective component based on anecdotal experience of the treating surgeon, which may lead to variable treatment algorithms that lack consensus opinion [ 18 , 19 ]. Inaccurate assessment may affect the timing of surgery and is highly correlated with soft tissue complications and longer hospitalization [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fractures caused by low-energy indirect trauma are generally treated conservatively, but when conservative treatment fails to restore joint consistency and fractures are caused by high-violent trauma, surgical reduction is the preferred treatment method ( Goost et al, 2014 ). The most commonly used surgical treatment is open reduction and internal fixation (ORIF), the main purpose of which is to prevent posttraumatic arthritis and shorten the immobilization time ( Tantigate et al, 2019 ). The severity of the injury, surgical intervention and fixation time all contribute to biomechanical changes ( Egol et al, 2006 ), and recovery of these parameters after ankle treatment is critical.…”
Section: Application In Foot and Ankle Diseasesmentioning
confidence: 99%